Principal's Leadership Strategy in Realizing Inclusive Education Policy - Parnoningrum, Triworo; Hariyati, Nunuk; Sholeh, Muhammad; Hazin, Mufarrihul; Purwoko, Budi (SAINTIS Publishing, 2025)
The purpose of this study is to describe the principal's leadership in managing inclusive schools, related to the principal's policy, curriculum and learning management, learning assessment, and inclusive culture. This study was conducted through a qualitative approach with a multi-site design using a constant comparative technique at SMP Negeri 29 Surabaya City, and SMP Negeri 5 Surabaya City. The research findings indicate that the principal's leadership in formulating inclusive school policies is based on government appointments. Inclusive curriculum management is in the form of a curriculum that is modified according to the characteristics and needs of students, including aspects of objectives, sources, materials, media, schedules, and assessments. Learning leadership is carried out collaboratively between subject teachers, GPK, BK teachers, and homeroom teachers. Student assessments take into account the conditions of students with and without disabilities. The development of an inclusive culture is carried out through learning, scouting activities, self-development and extracurricular activities. The principal's leadership emphasizes the value for school personnel to have confidence in carrying out tasks, high commitment, and enthusiasm to help the community get decent education inclusively, which has an impact on the development of inclusive education in schools.